Review of the Economy 2012/13 Economic Advisory Council to the Prime Minister New Delhi April 2013 - Economic Advisory Council to the Prime Minister Planning Commission (Economic Advisory Council to the Prime Minister Planning Commission Government of India, 2013)
The Review of the Economy 2012-13, published by the Economic Advisory Council to the Prime Minister in April 2013, presents a comprehensive assessment of India’s macroeconomic performance during a year marked by significant slowdown and structural imbalances. GDP growth decelerated sharply to about 5.0 percent against an earlier projection of 6.7 percent, while inflation remained persistent, with Wholesale Price Index inflation averaging 7.3 percent and Consumer Price Index inflation staying in double digits due largely to rising food and housing costs. A major concern was the widening Current Account Deficit, which rose to nearly 5 percent of GDP and peaked at 6.7 percent in the third quarter, driven by a large merchandise trade deficit of $195 billion and elevated imports of oil and gold. Although gross domestic capital formation remained relatively strong at 35.4 percent of GDP, declining household financial savings and increased gold purchases exposed a widening savings-investment gap. The fiscal situation also remained strained, with the combined fiscal deficit of the Centre and States reaching about 7 percent of GDP and subsidies—particularly petroleum subsidies—rising sharply. Monetary policy responses by the Reserve Bank of India included earlier repo rate hikes followed by calibrated rate cuts in early 2013 amid tight liquidity conditions. Looking ahead to 2013-14, growth was projected to recover to 6.4 percent contingent upon improved investment conversion, policy reforms, and better project implementation. The report emphasizes urgent structural reforms, including expediting project clearances, rationalizing subsidies, curbing gold and oil imports, strengthening export performance, reforming agricultural marketing systems, and improving fiscal management to restore macroeconomic stability and place India on a sustainable higher growth trajectory.
Economic Advisory Council to the Prime Minister E-Hall Vigyan Bhawan
Keywords: Review of the Economy 2012-13; Economic Advisory Council to the Prime Minister; GDP Growth; Inflation Trends; Current Account Deficit; Fiscal Deficit; Gross Domestic Capital Formation; Merchandise Trade Deficit; Reserve Bank of India; Monetary Policy; Subsidy Reform; Economic Reforms